A many-sided life: cadreman, educationalist, theorist and practitioner of physical education, researcher, personality that defines Olympic movement - Bubka S.N (Kharkov National Pedagogical University, 2012)
This article highlights the foremost landmarks in the life and work of a prominent expert in the field of physical education and sport, an active participant of the Olympic Games revival and one of the members of the 1st International Olympic Committee Alexey Butovsky. His military career from a cadet and non-commissioned officer to lieutenant-general is outlined, and his activities in the field of theory and practice of physical education both in Russia and on his trips abroad, which was aimed at study, generalization and further application of the best experience accumulated in that area in different countries, are presented, as well. A. Butovsky's acquaintance with P. de Coubertin and their closer relations resulted in Alexey Butovsky's involvement in the preparation and participation of the founding congress in 1894 in Paris is particularly noted, as well as the Congress that adopted important decisions on the revival of the Olympic Games and creation of the International Olympic Committee, in which General Butovsky was introduced among its first members. There has been studied his activity not only as a member of the IOC, but his doings after his retirement from the membership of this international organization, as well.